Partner's age, not social environment, predicts extrapair paternity in wild great tits (Parus major). (27th September 2019) - Roth, Allison M; Firth, Josh A; Patrick, Samantha C; Cole, Ella F; Sheldon, Ben C
Abstract: An individual's fitness is not only influenced by its own phenotype, but by the phenotypes of interacting conspecifics. This is likely to be particularly true when considering fitness gains and losses caused by extrapair matings, as they depend directly on the social environment. While previous work has explored effects of dyadic interactions, limited understanding exists regarding how group-level characteristics of the social environment affect extrapair paternity (EPP) and cuckoldry. We use a wild population of great tits ( Parus major ) to examine how, in addition to the phenotypes of focal parents, two neighborhood-level traits—age and personality composition—predict EPP and cuckoldry. We used the well-studied trait "exploration behavior" as a measure of the reactive-proactive personality axis. Because breeding pairs inhabit a continuous "social landscape, " we first established an ecologically relevant definition of a breeding "neighborhood" through genotyping parents and nestlings in a 51-ha patch of woodland and assessing the spatial predictors of EPP events. Using the observed decline in likelihood of EPP with increasing spatial separation between nests, we determined the relevant neighborhood boundaries, and thus the group phenotypic composition of an individual's neighborhood, by calculating the point at which the likelihood of EPP became negligible. We found no evidence that "social environment" effects (i.e., neighborhood age or personality composition) influenced EPP or cuckoldry. We did, however, find that a female's own age influenced the EPP of her social mate, with males paired to older females gaining more EPP, even when controlling for the social environment. These findings suggest that partner characteristics, rather than group phenotypic composition, influence mating activity patterns at the individual level. Abstract : Mating activity may be influenced by the traits of one's self, one's partner, or one's social environment. Males increase the number of genes they pass on by mating with females other than their partner. We show that, in great tits, males are more likely be unfaithful to an older partner, and males typically breed with extrapair females whose nests are closer. Interestingly, the average trait values of a male's neighbors did not influence his extrapair paternity.